2020
DOI: 10.1093/crocol/otaa002
|View full text |Cite
|
Sign up to set email alerts
|

TELEmedicine for Patients With Inflammatory Bowel Disease (TELE-IBD) Does Not Improve Depressive Symptoms or General Quality of Life Compared With Standard Care at Tertiary Referral Centers

Abstract: Background Depression is common in patients with inflammatory bowel disease (IBD) and contributes to poor quality of life (QoL). The use of information technology for the remote management of patients with IBD is growing, but little is known about its impact on depressive symptoms (DS) and QoL. We aimed to evaluate the impact of telemedicine on DS and generic QoL in IBD patients. Methods We analyzed data from the Telemedicine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 41 publications
0
22
0
Order By: Relevance
“…The following publications were excluded: 12 articles because of a lack of accessible full text, 13 because of incomplete data, 7 for being unrelated to the topic, and 11 for failure of randomization; 21 conference abstracts; and 13 reviews. Finally, 17 RCTs were considered potentially eligible and comprised 2571 patients from 2010 to 2020; most of these RCTs were conducted in the United States [39][40][41][42][43][44][45], followed by the Netherlands [46][47][48], New Zealand [49,50], Denmark [12,51], the United Kingdom [52], Spain [53], Ireland [12], and Turkey [13]. The process of selecting enrolled studies is shown in Figure 1.…”
Section: Search Process Study Characteristics and Quality Assessmentmentioning
confidence: 99%
“…The following publications were excluded: 12 articles because of a lack of accessible full text, 13 because of incomplete data, 7 for being unrelated to the topic, and 11 for failure of randomization; 21 conference abstracts; and 13 reviews. Finally, 17 RCTs were considered potentially eligible and comprised 2571 patients from 2010 to 2020; most of these RCTs were conducted in the United States [39][40][41][42][43][44][45], followed by the Netherlands [46][47][48], New Zealand [49,50], Denmark [12,51], the United Kingdom [52], Spain [53], Ireland [12], and Turkey [13]. The process of selecting enrolled studies is shown in Figure 1.…”
Section: Search Process Study Characteristics and Quality Assessmentmentioning
confidence: 99%
“…A high proportion of patients were satisfied and would maintain remote monitoring; patients with IBD seem to have a good perception of telemedicine, as suggested by other studies, even if with conflicting results [32,33], and this attitude is not limited to the youngest and so-called "digital native" patients. Telemedicine could be the COVID-19 legacy in the management of IBD, aiming to reduce the cost of patients' care and rationalize the use of health resources with the standardization of infrastructures and costs [34,35]. Moreover, IBDs are heterogeneous diseases, with about half of the patients experiencing a mild disease, while 20-30% of patients develop an aggressive course: telemedicine can maintain an adequate follow-up and a satisfying patient-doctor relationship while traditional consultations are provided to severe disease and to recent-onset disease, where talking with the doctor in person is a more effective way of providing health care (need of physical examination, of point-of-care texts such as ultrasound, empathy with the doctor).…”
Section: Discussionmentioning
confidence: 99%
“…The development of more advanced platforms of telemedicine with a strict observance of GDPR (general data protection regulation) and cybersecurity rules is also warranted. Although initial investments in resources, software, training, and maintenance will be necessary at the beginning, telemedicine is going to be, in the long term, helpful for health organizations to reduce the burden associated with IBD [34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…The improvement in QoL could be attributed to the absence of hospital contacts, reducing stress for the patients in the tele-monitoring group. On one hand, the lack of clinical visits in person could only partially be replaced by the remote video assistance needed to avoid the potential risk of Covid-19 infection, and it is clear that direct interaction between clinicians and patients heavily affects the mental health and the depressive status of these patients, with downstream effects on the individual lifestyle and quality of life that are so important for the subjective patient outcome [ 13 ]. On the other hand, the possibility to contact clinicians “on demand” through the video assistant likely contributed to ensure the maintenance of the QoL parameter even in the absence of direct, classical interaction with the physician, in the overwhelmingly difficult situation of the SARS-CoV-2 pandemic.…”
Section: Discussionmentioning
confidence: 99%